GLOBAL TOURIST BEHAVIOR TRENDS IN THE NEW NORMAL ERA: REVENGE TOURSM PERSPECTIVE - putra, yogi; Elfitra Desy Surya; Sitorus, Syahrial; Barus, Apriwati (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study evaluates the relationship between memorable tourism experience, destination image, Place Attachment, Destination Accessibility, and Destination Quality Tourism Revenger Tourism influence related to Destination Loyalty. Using data from 370 self-administered questionnaires from two tourist attractions of interest in North Sumatra, Indonesia. Partial Least Squares Modeling is used to assess the hypotheses developed. Results reveal the significant impact of wellness tourism, Online Review of Tourist Destination, Characteristics of Destination Image, Memorable Tourist Experience, and revenue Tourism on destination loyalty. The purpose of this study further highlight the indirect effects of wellness tourism, Online Reviews of Tourist Destinations, Characteristics of Destination Image, and Memorable Tourist Experience on destination loyalty. Conceptually, this study offers a new understanding of the formation of tourist loyalty in the growth context of revenge tourism and the managerial implications of these findings discussed.